Different impact of bovine complement regulatory protein 46 (CD46bov) as a cellular receptor for members of the species Pestivirus H and Pestivirus G. Issue 1 (31st December 2022) - Leveringhaus, Elena; Cagatay, Gökce Nur; Hardt, Juliane; Becher, Paul; Postel, Alexander
ABSTRACT: The genus Pestivirus within the family Flaviviridae comprises highly relevant animal pathogens such as bovine viral diarrhoea virus 1 and 2 (BVDV-1 and -2) classified into the two species Pestivirus A and Pestivirus B, respectively. First described in 2004, HoBi-like pestiviruses (HoBiPeV) represent emerging bovine pathogens that belong to a separate species ( Pestivirus H ), but share many similarities with BVDV-1 and -2. Additionally, two giraffe pestivirus (GPeV) strains both originating from Kenya represent another distinct species ( Pestivirus G ), whose members replicate very efficiently in bovine cells. In this study, we investigated the role of bovine complement regulatory protein 46 (CD46bov ), the receptor of BVDV-1 and -2, in the entry of HoBiPeV and GPeV. For this purpose, bovine CD46-knockout and CD46-rescue cell lines were generated by CRISPR/Cas9 technology and subsequent trans-complementation, respectively. Our results provide strong evidence that the impact of CD46bov differs between viruses belonging to Pestivirus H and viruses representing Pestivirus G : CD46bov revealed to be a major cellular entry factor for HoBiPeV strain HaVi-20. In contrast, GPeV strain PG-2 presented as largely independent of CD46bov, suggesting a different entry mechanism involving other molecular determinants which remain to be identified. In addition, we demonstrated that, similar to BVDV-1 and -2, virus isolates of both Pestivirus H and Pestivirus G are able to adapt to cell culture conditions by using heparan sulfate to enter the host cell. In conclusion, our findings show that different bovine pestiviruses use diverse mechanisms of host cell entry.